Effective Leadership Development to Enhance the Capacity of Social Organizations to Respond to Complex Social Challenges - Corte-Real, José Mendes; Khairi, Muhammad; Khayru, Rafadi Khan (Journal of Social Science Studies, 2021)
Effective leadership development in social organizations is key to enhance the organization’s capacity to respond to social challenges. Responsive, adaptive and inclusive leadership helps social organizations to deal with dynamic social change. This involves continuous training, member empowerment, and collaborative team management. The utilization of technology and social networks is an important element in supporting leadership effectiveness. Continuous evaluation is also needed to assess progress and ensure that leadership development strategies remain relevant. By strengthening leadership capacity, social organizations can be more efficient in dealing with social problems and providing appropriate solutions. Social organizations need to develop leadership that is not only competent, but also visionary, capable of leading the organization towards better and fairer changes.